NUTRITIONAL ASSESSMENT OF HEMODIALYSIS PATIENTS - Anum Manzoor; Safia Shahid; Waqar Ahmad; et al. (Pakistan Journal of Kidney Diseases, 2021)
Introduction: Malnutrition is common in hemodialysis patients and closely related to morbidity and mortality. Therefore, assessment of nutritional status and nutritional management of hemodialysis patients play a central role. Methods: This study is carried out in three different dialysis centers of Lahore, to determine the frequency and severity of malnutrition in dialysis patients, to evaluate the dietary approach and dietary compliance of dialysis patients, and to recommend an appropriate dietary modality for dialysis patients. For enlightening the quality of life and for decreasing the complications Medical Nutrition Therapy is very important in dialysis patients. This study is based on the nutritional assessment of dialysis patients. It will provide the information about the current nutritional status of dialysis patients whether the patient is well nourished, moderately malnourished or severely malnourished. To assess the biochemical values for sodium, potassium, albumin levels, hemoglobin levels, TIBC levels, iron levels, urea levels and creatinine levels. To assess the diet history, anthropometric measurements, physical examination and life style factors of dialysis patients are also included in this study